AlxGa1−xN‐Based Quantum Wells Fabricated on Macrosteps Effectively Suppressing Nonradiative Recombination. Issue 2 (4th December 2018) - Hayakawa, Minehiro; Ichikawa, Shuhei; Funato, Mitsuru; Kawakami, Yoichi
Abstract: Al x Ga1− x N‐based quantum wells (QWs) are fabricated on AlN with macrosteps, which are formed by using vicinal sapphire and AlN (0001) substrates. The QWs on macrosteps (MS‐QWs) show photoluminescence lifetimes of nearly 2 ns at an emission wavelength of 242 nm at room temperature (RT). This is the longest lifetime so far reported for Al x Ga1− x N‐based QWs emitting below 270 nm, indicating the suppression of nonradiative recombination, the dominant recombination process at RT. Compared with planar QWs without macrosteps, the emission internal quantum efficiency estimated by photoluminescence spectroscopy is improved approximately by two orders of magnitude under a weak excitation condition. Consequently, Al x Ga1− x N‐based MS‐QWs are promising structures for highly efficient ultraviolet emitters. Abstract : Al x Ga1− x N‐based quantum wells (QWs) fabricated on AlN with macrosteps show nonradiative recombination lifetimes of ≈2 ns at 242 nm wavelength at room temperature. This long lifetime indicates suppressed nonradiative recombination processes. Compared with conventional QWs without macrosteps, QWs on macrosteps have the emission efficiency improved approximately by two orders of magnitude, showing promise as highly efficient ultraviolet emitters.